Reaching Out – And Back - Hemann, Patricia A.; Morgenstern-Clarren, Pat E. (Columbia Journal of Gender and Law, 2000)
Like many good ideas, the Women’s Leadership Lecture Series was born out of both creativity and desperation. Our story takes place in 1990 when we were partners in a large law firm-but we must first back up to the early 1980s. In our experience, that time heralded the end of “law as a noble profession” and the beginning of the era of “law as a business.” Law firms started to grow rapidly. For the first time, a significant part of that growth came from persuading lawyers to move from one firm to another. The lawyers sought out for those transfers were the ones with a book of business. Financial rewards, which had always been based on the number of years of service to the firm, now followed those who had their own clients. The notion that firms were loyal to their partners, associates, and staff, and vice versa, began to unravel. And as it unraveled, it became imperative to have one’s own clients. Our firm was not immune to this change. The idea that it was enough to be a good lawyer, that business and success would follow, was lost. The impact was felt by all, but particularly by the women lawyers. Traditionally, when all large law firm lawyers were men, the older lawyers taught their male protégés how to bring in and maintain business by a process akin to osmosis. They took them to lunch, to visit clients, to court, to charitable events, and to play golf. They arranged for them to be appointed to boards of trustees where valuable contacts were made. In short, they created relationships that were strong and longstanding so that when the older lawyer retired, the younger man stepped effortlessly into his shoes and into the client billings. This system historically worked well for both the firms and the lawyers, but it fell apart when women came into law firms in large numbers.